Assessing The Challenges Pertaining To The Adoption And Implementation Of Affirmative Action And Its Impact On Female Empowerment In Some Selected Tertiary Institutions In Ghana - Taylor, T. (University of Ghana, 2016)
The study was designed to assess the challenges pertaining to the adoption and implementation of Affirmative Action Practices and its impact on Female Empowerment in some selected Tertiary Institution in Ghana. The universities used for the study were, University of Ghana, Legon (UG), Kwame Nkrumah University of Science and Technology (KNUST) and University of Education, Winneba (UEW). The study adopted the qualitative research approach, using explanatory and descriptive research designs. The targeted population of the study was senior members and beneficiaries of the affirmative action practices of the selected tertiary institutions. Purposive sampling technique was used in selecting a total of thirty (30) respondents for the study and a semi-structured interview guide was used in collecting data. The study revealed that respondent‘s knowledge of affirmative action practices in their respective universities is high. The study again showed that only University of Education, Winneba had a working document on gender policy as well as a caption of gender related issues in their strategic plan whereas, UG, and KNUST only had it captured in their strategic plans. Again, the study found out that all the universities had a clear cut out plan of opportunities for advancement and access to information and support to all female staff and students. Based on the finding, the study recommends that UG and KNUST should have a working document on affirmative action to aid its implementation. The study again recommends that sensitization programmes should be organised to increase staff awareness of the affirmative action policy. Finally the study recommends that support resources and information should be provided for deserving women to work as their male counterparts to eliminate discrimination and promote gender parity in the institutions.
Thesis (MPhil)
Keywords: Challenges; Adoption; Implementation; Affirmative Action; Female Empowerment; Selected Tertiary Institutions; Ghana